Be as careful of the books you read as of the company you keep: evidence on peer effects in educational choices - Giacomo De Giorgi; Michele Pellizzari; Silvia Redaelli (Institute for the Study of Labor (IZA), 2007)
In this paper we investigate whether peers' behavior influences the choice of college major. Using a unique dataset of students at Bocconi University and exploiting the organization of teaching at this institution, we are able to identify the endogenous effect of peers on such decision through a novel identification strategy which solves the common econometric problems of studies of social interactions. Results show that, indeed, one is more likely to choose a major when many of her peers make the same choice. We estimate that, when it diverts students from majors in which they seem to have a relative ability advantage, this effect leads to lower average grades and graduation mark, a penalty that could cost up to 1,117 USD a year in the labor market
urn:nbn:de:101:1-2008032811
Keywords: 330; Bildungsverhalten; Soziale Beziehungen; Bildungsertrag; Italien